2012
DOI: 10.1111/j.1365-2958.2012.08131.x
|View full text |Cite
|
Sign up to set email alerts
|

Relaxosome function and conjugation regulation in F‐like plasmids – a structural biology perspective

Abstract: Summary The tra operon of the prototypical F plasmid and its relatives enables transfer of a copy of the plasmid to other bacterial cells via the process of conjugation. Tra proteins assemble to form the transferosome, the transmembrane pore through which the DNA is transferred, and the relaxosome, a complex of DNA‐binding proteins at the origin of DNA transfer. F‐like plasmid conjugation is characterized by a high degree of plasmid specificity in the interactions of tra components, and is tightly regulated at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
63
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(63 citation statements)
references
References 138 publications
(225 reference statements)
0
63
0
Order By: Relevance
“…Structural studies have determined that the last 7 amino acids (V 712 EPGDDF 717 ) of TraD's CTD fit into a positively charged groove of TraM. Further mutational analyses of this partner interaction confirmed that the TraD CTD-TraM interaction is required for highly efficient F plasmid transfer and, conversely, is strongly inhibitory for F plasmid mobilization of MOBQ plasmids (68,69). These findings warrant further studies exploring the importance of the CTDs of PcfC pCF10 , VirD4 At , and other T4CPs that carry such domains for possible DNA or effector protein contacts.…”
Section: Discussionmentioning
confidence: 85%
“…Structural studies have determined that the last 7 amino acids (V 712 EPGDDF 717 ) of TraD's CTD fit into a positively charged groove of TraM. Further mutational analyses of this partner interaction confirmed that the TraD CTD-TraM interaction is required for highly efficient F plasmid transfer and, conversely, is strongly inhibitory for F plasmid mobilization of MOBQ plasmids (68,69). These findings warrant further studies exploring the importance of the CTDs of PcfC pCF10 , VirD4 At , and other T4CPs that carry such domains for possible DNA or effector protein contacts.…”
Section: Discussionmentioning
confidence: 85%
“…pSK41-like conjugative plasmids have also been shown to mobilize several smaller coresident plasmids, such as pC221 and pSK639, which carry their own mob genes (9,12,13,15,16). Recently, O'Brien et al showed that another staphylococcal conjugative plasmid, pWBG749, which is unrelated to pSK41, can facilitate the mobilization of other plasmids that lack mob genes (17).…”
mentioning
confidence: 99%
“…A relaxase is responsible for initiation and completion of the transfer process, as it cleaves one strand of the double-stranded plasmid to begin transfer and then ligates the strands back together to complete transfer (8,(12)(13)(14)(15). There are two classes of relaxases: multityrosine relaxases, which use a "thumb" motif to position the plasmid DNA for processing, and single-tyrosine relaxases, which lack this thumb motif (9,16). The relaxase of pSK41 is termed the NES nicking enzyme in S. aureus, and it is a single-tyrosine relaxase (1-6, 8, 9).…”
mentioning
confidence: 99%
“…During recent years, the way in which a complex network of plasmid and host encoded factors regulate tra gene expression in F-like plasmids has been intensively studied (Frost & Koraimann, 2010;Wong et al, 2012). Of note, all of the F-like plasmids characterized to some degree (such as R1, R100, pSLT, p307) carry a repressor system (FinOP) that disables expression of the tra operon in the majority of cells (.99 %) within a population.…”
Section: Introductionmentioning
confidence: 99%